Методы и технологии развития толерантности личности - Демисенова, Ш.С.; Ахметбекова, З.Д.; Аманова, Ж.С. (My University, 2016)
This article is dedicated to the students’ forming of the polycultural tolerance in pedagogical schools. The methods and techniques of multicultural tolerance.
Keywords: tolerance method; technique